Non-noble metal fuel cell oxygen reduction catalyst based on self-assembled semi-interpenetrating polymer network as well as preparation method and application of non-noble metal fuel cell oxygen reduction catalyst

Through self-assembly semi-interpenetrating polymer network hydrogel technology, iron ions are anchored and pyrolysis is used to form a high load, atomic dispersion of non-precious metal fuel cell oxygen reduction catalyst, which solves the problems of high cost of precious metals, low active site density and poor stability in the prior art, and achieves a high stability and high activity catalyst.

CN119650729AActive Publication Date: 2025-03-18HAINAN UNIV

Patent Information

Application Number
CN202510091906.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-03-18
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The existing fuel cell cathode oxygen reduction catalysts have problems such as high cost of precious metals, low density of active sites and poor stability. They are especially easy to dissolve in an acidic environment, which affects the activity and stability of the catalyst.

Method used

By anchoring iron ions after polymerization using inexpensive polysaccharides and polymer monomers, self-assemble to form a semi-interpenetrating polymer network hydrogel, and a high load and atomically dispersed non-precious metal fuel cell oxygen reduction catalyst is formed by pyrolysis.

Benefits of technology

The high stability and high activity of the catalyst are achieved, the use of precious metals is avoided, the utilization rate of metal atoms is improved, and good performance is maintained in an acidic environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650729A_ABST
    Figure CN119650729A_ABST
Patent Text Reader

Abstract

The invention relates to a non-noble metal fuel cell oxygen reduction catalyst based on a self-assembled semi-interpenetrating polymer network and a preparation method and application thereof, and belongs to the technical field of fuel cell oxygen reduction catalysts. The preparation method of the catalyst comprises the following steps: S1, dissolving polysaccharide in ultrapure water, heating and stirring, then adding a polymer monomer, a polymerization initiator, a salt template and a non-noble metal source solution, heating and stirring until uniform orange red hydrogel is obtained, then adding a nitrogen source, continuously heating and stirring, and evaporating a solvent to dryness, so as to obtain a polysaccharide solution; freezing and drying to obtain an orange powder sample; s2, performing pyrolysis treatment on the orange powder sample to obtain a black powder sample, and performing acid pickling, suction filtration and drying to obtain a precursor product; s3, pyrolyzing the precursor product again to obtain the catalyst. The semi-interpenetrating polymer network hydrogel is synthesized in a self-assembly mode, and the catalyst with high loading capacity and atomic-scale dispersion is formed through pyrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of fuel cell oxygen reduction catalysts, and in particular to a non-precious metal fuel cell oxygen reduction catalyst based on a self-assembled semi-interpenetrating polymer network, and a preparation method and application thereof. Background Art

[0002] At present, under the background of global energy transformation and my country's clean and low-carbon energy transformation, hydrogen energy development and utilization technology represented by fuel cells has made major breakthroughs. However, the slow rate of oxygen reduction reaction (ORR) at the cathode of fuel cells has seriously hindered its development. To date, platinum (Pt)-based catalysts are still the most commonly used and efficient catalysts for ORR, but their high cost and easy poisoning characteristics have largely hindered their large-scale application. Therefore, the development of various inexpensive, highly active and stable transition metal-based and metal-free catalysts as alternatives to Pt-based catalysts has received widespread attention.

[0003] Co-pyrolysis of metal organic frameworks (MOFs) and transition metal sources at high temperatures is a common method for synthesizing transition metal-nitrogen-carbon (MNC, M=Fe, Co, Mn, etc.) catalysts, but there are still some challenges that prevent it from fully meeting industrial needs. One of the challenges is that the coordinated metals in MOFs are not completely sublimated during the pyrolysis process, resulting in insufficient defects in the MOF matrix, leading to a low density of active sites. In addition, MNC catalysts prepared based on MOFs usually confine the metal in the MOF cavity, which easily causes the metal to sinter and agglomerate to form micro / nanoparticles during pyrolysis. These aggregated particles not only reduce the utilization rate of metal atoms, but are also easily dissolved in an acidic environment, thereby affecting the activity and stability of the catalyst. Therefore, it is necessary to develop methods that can accurately anchor and disperse metal ions to avoid the defects of the above synthesis methods. At present, some studies use a large number of functional groups in monomer hydrogels to anchor metal ions in an "egg-box" structure, and form atomically dispersed MNC catalysts through subsequent pyrolysis. However, due to the single pore structure of this type of monomer hydrogel and the insufficient chelation strength between it and the metal ions, the catalyst after pyrolysis still has an inhomogeneous metal-nitrogen coordination structure (such as partially unstable Fe-N 2 / N 3 sites), mass transfer and diffusion limitations, etc. Summary of the invention

[0004] In view of this, the present application provides a non-precious metal fuel cell oxygen reduction catalyst based on a self-assembled semi-interpenetrating polymer network, and a preparation method and application thereof, wherein cheap polysaccharides (taking carboxymethyl chitosan (CMCS), sodium carboxymethyl starch (CMS), and hydroxypropyl cellulose (HPC) as examples) and polymer monomers (acrylamide (AM), acrylonitrile (AN), and fumaric acid (FA), taking AM as an example) are polymerized to anchor iron ions, and a semi-interpenetrating polymer network hydrogel is synthesized by self-assembly, and a high-load and atomically dispersed catalyst is formed by pyrolysis; the entire synthesis process does not require the assistance of any high-temperature and high-pressure equipment, and the new synthesis route has high atomic utilization and simple process, which can provide a new idea for the commercial large-scale production of high-efficiency oxygen reduction catalysts. The catalyst prepared in the present application has the advantages of high stability and high activity, and can effectively overcome the defects of the above-mentioned prior art.

[0005] The first aspect of the present application provides a method for preparing a non-precious metal fuel cell oxygen reduction catalyst based on a self-assembled semi-interpenetrating polymer network, comprising the following steps:

[0006] S1. Dissolve the polysaccharide in ultrapure water, heat and stir, then add the polymer monomer, polymerization initiator, salt template and non-precious metal source solution, heat and stir until a uniform orange-red hydrogel is obtained, then add the nitrogen source, continue heating and stirring, evaporate the solvent, and freeze-dry to obtain an orange powder sample;

[0007] S2, pyrolyzing the orange powder sample to obtain a black powder sample, and then washing with acid, filtering, and drying to obtain a precursor product;

[0008] S3. The precursor product is pyrolyzed again to obtain a non-precious metal fuel cell oxygen reduction catalyst based on a self-assembled semi-interpenetrating polymer network.

[0009] Specifically, the steps include:

[0010] S1. Dissolve the polysaccharide in ultrapure water, heat and stir, then add the polymer monomer, azobisisobutylamidine hydrochloride, sodium chloride and ferric nitrate solution, heat and stir until a uniform orange-red hydrogel is obtained, then add urea, continue heating and stirring, evaporate the solvent, and freeze-dry to obtain an orange powder sample;

[0011] S2, pyrolyzing the orange powder sample to obtain a black powder sample, and then washing with acid, filtering, and drying to obtain a precursor product;

[0012] S3. The precursor product is pyrolyzed again to obtain a non-precious metal fuel cell oxygen reduction catalyst based on a self-assembled semi-interpenetrating polymer network.

[0013] The present application introduces an additional non-crosslinked linear polymer on the basis of the monomer hydrogel to construct a hydrogel with a semi-interpenetrating polymer network. Compared with the monomer hydrogel, the semi-interpenetrating polymer network hydrogel has chemical and physical double crosslinks. The chemical crosslinking can form a relatively stable network, and the presence of physical crosslinking increases the flexibility and dynamics of the network. This semi-interpenetrating polymer network allows a large number of crosslinking points to exist inside the hydrogel, which can achieve more effective anchoring of metal ions, so that the catalyst after pyrolysis has a more stable Fe-N 4 / C active sites and richer three-dimensional micropore / mesopore / macroporous structure further improve the stability of the catalyst and the mass transfer of reactants / products.

[0014] Preferably, in step S2, the specific conditions of the pyrolysis are: placing the orange powder sample in a tube furnace, heating it to 700-1000° C. at a heating rate of 10° C. / min under an argon atmosphere, and pyrolyzing it at this temperature for 3 hours; or

[0015] In step S3, the specific conditions of the pyrolysis are: heating to 700-1000°C at a heating rate of 10°C / min under an argon atmosphere, and pyrolyzing at this temperature for 3h.

[0016] Preferably, in step S2, the specific conditions of the pickling are: at 120°C, 500 mL of 1M H 2 SO 4 Acid washing in solution.

[0017] Preferably, in step S1, the polysaccharide is selected from carboxymethyl chitosan, sodium carboxymethyl starch, and hydroxypropyl cellulose; or

[0018] In step S1, the polymer monomer is selected from acrylamide, acrylonitrile, fumaric acid; or

[0019] In step S1, the heating and stirring temperature is 50-80°C.

[0020] Preferably, the usage ratio of the polysaccharide, ultrapure water, polymer monomer, azobisisobutylamidine hydrochloride, sodium chloride, ferric nitrate and urea is (1.0-4.0g):500mL:(0.5-2.0mL):(0.05-0.2g):3.0g:(0.5-1.0g):(0.5-2.0g).

[0021] Preferably, in step S1, the polymerization initiator is selected from one of azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, and azobisisopropylimidazoline; or

[0022] The salt template is selected from one of sodium chloride, sodium carbonate, sodium sulfate, potassium chloride and potassium sulfate; or

[0023] The non-precious metal source is an iron salt, and the iron salt is selected from one of iron nitrate, iron chloride and iron sulfate; or

[0024] The nitrogen source is selected from one of urea, aniline, melamine and dicyandiamide.

[0025] The second aspect of the present application also provides a non-precious metal fuel cell oxygen reduction catalyst based on a self-assembled semi-interpenetrating polymer network, which is prepared by the above method.

[0026] The third aspect of the present application also provides the use of the above-mentioned non-precious metal fuel cell oxygen reduction catalyst based on the self-assembled semi-interpenetrating polymer network in the battery cathode material.

[0027] The fourth aspect of the present application also provides a working electrode, comprising the above-mentioned non-precious metal fuel cell oxygen reduction catalyst based on self-assembled semi-interpenetrating polymer network.

[0028] The fifth aspect of the present application also provides a method for preparing the above-mentioned working electrode, comprising the following steps:

[0029] The non-precious metal fuel cell oxygen reduction catalyst based on the self-assembled semi-interpenetrating polymer network, membrane solution and solvent are mixed in a certain proportion, ultrasonically treated to form a uniformly dispersed slurry, and the slurry is drop-coated on a disk / ring disk electrode to obtain a working electrode.

[0030] Compared with the prior art, this application has the following beneficial effects:

[0031] The present application uses cheap polysaccharides (taking carboxymethyl chitosan (CMCS), sodium carboxymethyl starch (CMS), and hydroxypropyl cellulose (HPC) as examples) and polymer monomers (acrylamide (AM), acrylonitrile (AN), and fumaric acid (FA), taking AM as an example) to anchor iron ions after polymerization, synthesizes a semi-interpenetrating polymer network hydrogel by self-assembly, and forms a high-load and atomically dispersed catalyst by pyrolysis; the entire synthesis process does not require the assistance of any high-temperature and high-pressure equipment, and the new synthesis route has high atomic utilization and simple process, which can provide a new idea for the commercial large-scale production of high-efficiency oxygen reduction catalysts; the catalyst prepared in the present application has the advantages of high stability and high activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions in the present application or the prior art, the drawings required for use in the description of the present application or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0033] Figure 1 TEM image of CMS-PAM-Fe-N catalyst;

[0034] Figure 2 XRD comparison diagrams of CMCS-PAM-Fe-N catalyst, CMS-PAM-Fe-N catalyst, HPC-PAM-Fe-N catalyst, and PAM-Fe-N catalyst;

[0035] Figure 3 The SCV comparison diagram of CMCS-PAM-Fe-N catalyst, CMS-PAM-Fe-N catalyst, HPC-PAM-Fe-N catalyst, and PAM-Fe-N catalyst;

[0036] Figure 4 This is a comparison chart of hydrogen peroxide yield and number of transferred electrons of CMCS-PAM-Fe-N catalyst, CMS-PAM-Fe-N catalyst, HPC-PAM-Fe-N catalyst, and PAM-Fe-N catalyst. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0038] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.

[0039] In the following examples and comparative examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.

[0040] Example 1

[0041] First, weigh 0.8g of ferric nitrate nine hydrate, add 10mL of ultrapure water, stir at room temperature until completely dissolved and set aside. Take 2.4g of carboxymethyl chitosan and add it to 500mL of ultrapure water, stir at 70℃ until completely dissolved, then add 1.1mL of acrylamide, followed by 0.1g of azobisisobutylamidine hydrochloride, and stir for 15min. Then add 3.0g of sodium chloride to the above solution, then slowly drip 10mL of ferric nitrate solution with a rubber-tipped dropper, and stir until a uniform orange-red hydrogel is obtained. Then add 1.0g of urea and continue stirring. Then evaporate the solvent until only about 80mL is left, stop heating, and freeze-dry to obtain an orange-yellow powder sample. Then place the powder sample in a tubular furnace and pyrolyze it for 3h at a heating rate of 10℃ / min and 800℃ under an argon atmosphere. After the pyrolysis is completed, a black powder sample is obtained. Then the black powder sample is heated at 120℃ and 500mL of 1M H 2 SO 4 The catalyst was then filtered with 3 L of water, dried, and pyrolyzed for a second time. The temperature was raised to 800 °C at a rate of 10 °C / min under an argon atmosphere, and pyrolyzed for 3 h at this temperature to obtain the CMCS-PAM-Fe-N catalyst, which was used for subsequent characterization and electrochemical testing.

[0042] Example 2

[0043] Except for the following steps which are different from those in Example 1, other preparation and testing methods are exactly the same as those in Example 1.

[0044] Take 2.0g of sodium carboxymethyl starch and add it to 500mL of ultrapure water, stir at 70℃ until it is completely dissolved, then add 1.1mL of acrylamide, followed by 0.05-0.2g of azobisisobutylamidine hydrochloride and stir for 15min. Then add 3.0g of sodium chloride to the above solution, then slowly drip 10mL of ferric nitrate solution with a rubber-tipped dropper and stir until a uniform orange-red hydrogel is obtained. Then add 1.0g of urea and continue stirring. Then evaporate the solvent until only about 80mL is left, stop heating, and freeze-dry to obtain an orange-yellow powder sample. Then place the powder sample in a tubular furnace and pyrolyze it for 3h at a heating rate of 10℃ / min and 800℃ under an argon atmosphere. After the pyrolysis is completed, a black powder sample is obtained. Then the black powder sample is heated at 120℃ and 500mL of 1M H 2 SO 4 The catalyst was then filtered with 3L of water, dried, and pyrolyzed for a second time. The temperature was raised to 800°C at a heating rate of 10°C / min under an argon atmosphere, and pyrolyzed for 3h at this temperature to obtain the CMS-PAM-Fe-N catalyst, which was used for subsequent characterization and electrochemical testing.

[0045] Example 3

[0046] Except for the following steps which are different from those in Example 1, other preparation and testing methods are exactly the same as those in Example 1.

[0047] Take 2.5g of hydroxypropyl cellulose and add it to 500mL of ultrapure water, stir at 70℃ until it is completely dissolved, then add 1.1mL of acrylamide, followed by 0.1g of azobisisobutylamidine hydrochloride, and stir for 15min. Then add 3.0g of sodium chloride to the above solution, then slowly drip 10mL of ferric nitrate solution with a rubber-tipped dropper, and stir until a uniform orange-red hydrogel is obtained. Then add 1.0g of urea and continue stirring. Then evaporate the solvent until only about 80mL is left, stop heating, and freeze-dry to obtain an orange-yellow powder sample. Then place the powder sample in a tubular furnace and pyrolyze it at 800℃ for 3h under an argon atmosphere at a heating rate of 10℃ / min. After the pyrolysis is completed, a black powder sample is obtained. Then the black powder sample is heated at 120℃ and 500mL of 1M H 2 SO 4 The catalyst was then filtered with 3L of water, dried, and pyrolyzed for a second time. The temperature was raised to 800°C at a heating rate of 10°C / min under an argon atmosphere, and pyrolyzed for 3h at this temperature to obtain the HPC-PAM-Fe-N catalyst, which was used for subsequent characterization and electrochemical testing.

[0048] Example 4

[0049] This embodiment can refer to the embodiment 1, except that the polymer monomer is acrylonitrile.

[0050] Example 5

[0051] This embodiment can refer to Example 1, except that the polymer monomer is fumaric acid.

[0052] Comparative Example 1

[0053] Add 1.0 mL of acrylamide solution to 500 mL of ultrapure water and stir at 70°C. Subsequently, add 0.8 g of ferric nitrate nonahydrate and 0.1 g of azobisisobutylamidine hydrochloride to the above solution in sequence and stir at 70°C until a uniform dark yellow gel suspension is obtained. Then, add 1.0 g of urea and continue stirring to evaporate the solvent to obtain an orange powder sample. The sample is then placed in a tubular furnace and pyrolyzed at 800°C for 3 hours at a heating rate of 10°C / min under an argon atmosphere. After the pyrolysis is completed, a black powder sample is obtained. The black powder sample is then heated at 120°C and 500 mL of 1MH 2 SO 4 The catalyst was then filtered with 3L of water, dried, and then pyrolyzed to obtain the PAM-Fe-N catalyst, which was used for subsequent characterization and electrochemical testing.

[0054] Test Case

[0055] The electrocatalyst materials in Examples 1-3 and Comparative Example 1 were mixed with membrane solution (nafion solution) and solvent (isopropanol / water (1:1)) in a ratio of catalyst: nafion solution: solvent = 10 mg: 40 μL: 1 mL, and then ultrasonicated for 30 min to form a uniformly dispersed slurry. 10 μL of the slurry was drop-coated on the disk / ring disk electrode to obtain a working electrode.

[0056] Depend on Figure 1 It can be seen that the CMS-PAM-Fe-N catalyst is an obvious porous sheet structure, and no Fe-related nanoparticles are observed.

[0057] Depend on Figure 2 It can be seen that the two broad diffraction peaks located at 24.1° and 43.3° correspond to partially graphitized carbon. Except for the diffraction peak of carbon, no peaks related to any other substances are observed, which indicates that Fe is distributed in the carbon carrier in the form of single atoms.

[0058] Depend on Figure 3 It can be seen that CMS-PAM-Fe-N exhibits the highest half-wave potential E 1 / 2 =0.80V vs.RHE.

[0059] Depend on Figure 4 It can be seen that Figure 4 The average H 2 O 2 The yield was less than 2% (in the potential range of 0.2-0.8 V vs. RHE); the electron transfer number (n) of all catalysts was greater than 3.95, indicating that all catalysts mainly converted O to 2 Reduction to H 2 O.

[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a non-precious metal fuel cell oxygen reduction catalyst based on a self-assembled semi-interpenetrating polymer network, characterized in that: The following steps are involved: S1. Dissolve the polysaccharide in ultrapure water, heat and stir, then add the polymer monomer, polymerization initiator, salt template and non-precious metal source solution, heat and stir until a uniform orange-red hydrogel is obtained, then add the nitrogen source, continue heating and stirring, evaporate the solvent, and freeze-dry to obtain an orange powder sample; S2, pyrolyzing the orange powder sample to obtain a black powder sample, and then washing with acid, filtering, and drying to obtain a precursor product; S3. The precursor product is pyrolyzed again to obtain a non-precious metal fuel cell oxygen reduction catalyst based on a self-assembled semi-interpenetrating polymer network.

2. The method for preparing a non-precious metal fuel cell oxygen reduction catalyst based on a self-assembled semi-interpenetrating polymer network according to claim 1, characterized in that: In step S2, the specific conditions of the pyrolysis are: placing the orange powder sample in a tube furnace, heating it to 700-1000° C. at a heating rate of 10° C. / min under an argon atmosphere, and pyrolyzing it at this temperature for 3 hours; or In step S3, the specific conditions of the pyrolysis are: heating to 700-1000°C at a heating rate of 10°C / min under an argon atmosphere, and pyrolyzing at this temperature for 3h.

3. The method for preparing a non-precious metal fuel cell oxygen reduction catalyst based on a self-assembled semi-interpenetrating polymer network according to claim 1, characterized in that: In step S2, the specific conditions of the pickling are: pickling in 500 mL of 1M H2SO4 solution at 120°C.

4. The method for preparing a non-precious metal fuel cell oxygen reduction catalyst based on a self-assembled semi-interpenetrating polymer network according to claim 1, characterized in that: In step S1, the polysaccharide is selected from one of carboxymethyl chitosan, sodium carboxymethyl starch, and hydroxypropyl cellulose; or In step S1, the polymer monomer is selected from acrylamide, acrylonitrile, fumaric acid; or In step S1, the heating and stirring temperature is 50-80°C.

5. The method for preparing a non-precious metal fuel cell oxygen reduction catalyst based on a self-assembled semi-interpenetrating polymer network according to claim 1, characterized in that: The usage ratio of the polysaccharide, ultrapure water, polymer monomer, azobisisobutylamidine hydrochloride, sodium chloride, ferric nitrate and urea is (1.0-4.0 g):500 mL:(0.5-2.0 mL):(0.05-0.2 g):3.0 g:(0.5-1.0 g):(0.5-2.0 g).

6. The method for preparing a non-precious metal fuel cell oxygen reduction catalyst based on a self-assembled semi-interpenetrating polymer network according to claim 1, characterized in that: In step S1, the polymerization initiator is selected from one of azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, and azobisisopropylimidazoline; or The salt template is selected from one of sodium chloride, sodium carbonate, sodium sulfate, potassium chloride and potassium sulfate; or The non-precious metal source is an iron salt, and the iron salt is selected from one of iron nitrate, iron chloride and iron sulfate; or The nitrogen source is selected from one of urea, aniline, melamine and dicyandiamide.

7. A non-precious metal fuel cell oxygen reduction catalyst based on a self-assembled semi-interpenetrating polymer network, characterized in that: A non-precious metal fuel cell oxygen reduction catalyst based on a self-assembled semi-interpenetrating polymer network prepared by the method described in any one of claims 1 to 6.

8. Use of the non-precious metal fuel cell oxygen reduction catalyst based on the self-assembled semi-interpenetrating polymer network as claimed in claim 7 in battery cathode materials.

9. A working electrode, characterized in that The invention comprises the non-precious metal fuel cell oxygen reduction catalyst based on the self-assembled semi-interpenetrating polymer network as described in claim 7.

10. A method for preparing the working electrode according to claim 9, characterized in that: The following steps are involved: The non-precious metal fuel cell oxygen reduction catalyst based on the self-assembled semi-interpenetrating polymer network, membrane solution and solvent are mixed in a certain proportion, ultrasonically treated to form a uniformly dispersed slurry, and the slurry is drop-coated on a disk / ring disk electrode to obtain a working electrode.

Citation Information

Patent Citations

  • Preparation method for oxygen reduction catalyst based on metal organic skeleton compound

    CN109638295A

  • Non-noble metal oxygen reduction electrocatalyst and preparation method thereof, and application of non-noble metal oxygen reduction electrocatalyst

    CN109950557A

  • Preparation method of high-density carbon-based bimetallic monatomic battery cathode material

    CN113745536A

  • Noble metal nanoparticles, a process for preparing these and their use

    US20020034675A1

Cited By

  • Electrolyte material of solid oxide electrolytic cell and preparation method of electrolyte material

    CN120348969A

  • Method for preparing platinum black catalyst with controllable particle size under assistance of amidine ligand

    CN120878871A